Self-Care Interventions as a Health Technology for Managing Type 2 Diabetes: A Population-Based Study in Iran - Zahra Yousefi Malekroodi; Seyed Ali Majidi; Amirmohammad Taalipasand (Health Technology Assessment in Action)
Background: The prevalence of type 2 diabetes represents a significant public health challenge, and effective disease management is essential for improving patient outcomes. Perceived social support and self-care are critical factors in the health of individuals with type 2 diabetes. Objectives: This study aimed to explore the relationship between social support, perceived stress, and self-care behaviors in patients with type 2 diabetes in Rasht. Methods: In this cross-sectional descriptive study, 384 participants were selected from a population of 40,000 people with type 2 diabetes in Rasht city, using the Karjesi and Morgan table. Tobert’s self-care questionnaires, the Perceived Social Support Scale by Zimmet, Dalhem, Zimmet, and Farley, and the Perceived Stress Scale by Cohen, Kamark, and Mermelstein were utilized for data collection. The data obtained from field investigations were analyzed using descriptive and analytical statistical tests, including Pearson correlation and linear regression, at a significance level of 0.01 and a confidence interval of 0.99, in SPSS software version 16. Results: The results of the study revealed a positive correlation between perceived social support and self-care (r = 0.35), family support and self-care (r = 0.25), friends’ support and self-care (r = 0.33), and support from significant individuals and self-care (r = 0.37). Conversely, a negative relationship was observed between perceived stress and self-care (r = -0.22). Conclusions: These findings can assist healthcare providers in expanding existing knowledge and designing diabetes self-care management education programs tailored to the psychosocial and cultural needs of adults in the study region.